Analysis of Variance and Standard Deviation of FM/M/1/k Interdependent Stochastic Feedback Arrival Model with Finite Capacity and Single Server - Gayathri, S.; Rani, G. (Communications in Mathematics and Applications, 2022)
In this paper, analysis of variance and standard deviation of interdependent stochastic feedback arrival rate and single server with service rate are considered. The steady-state solution and system characteristics are derived for this model. The effect of the nodal parameters on the system characteristics is established and using Maple software the analytical results are numerically illustrated and relevant conclusions are presented.